Acceptance as a Framework for a Successful Management of Land Use and Biological Diversity in Large Protected Areas - Ruschkowski, Eick von; Nienaber, Birte (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Local acceptance and the resolution of conflicts that arise from conservation objectives are important tasks for the successful management of large protected areas. This paper focuses on the distinct genesis of acceptance research for German large protected areas compared to the global context where the comprehensive term “park-people relationships” prevails. Using multiple tasks and roles assigned to national parks and biosphere reserves, we illustrate the overall diversity of conflict potential. Four explorative case studies, based on media analysis and selected expert interviews, are used to elaborate on the individual local conditions that foster conflict or co-existence in Germany. Berchtesgaden National Park is currently mainly free of conflicts, but unforeseen events such as barkbeetle infestations could unsettle the situation. On the contrary, private land ownership and conflicts over zoning in the Senne-Teutoburger Wald-Eggegebirge region have halted plans to establish a national park. In the Bliesgau Biosphere Reserve, conflicts arose around conflicting land uses and overlapping planning responsibilities during the designation process, while in the Pfälzerwald Biosphere Reserve region, the development of renewable energies – mainly wind turbines – have shown to bear a specific conflict potential. The paper concludes with suggestions related to spatial and environmental planning, such as widening the mainly local focus on “acceptance” to active stakeholder management, including integrated, adaptive management approaches, in the sense of the term park-people relationships.